2016
DOI: 10.5603/fm.a2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

The paranasal sinuses: three-dimensional reconstruction, photo-realistic imaging, and virtual endoscopy

Abstract: Background:The purpose of the study was to create computer-aided design models of the paranasal sinuses (frontal, maxillary, and sphenoid) (Folia Morphol 2016; 75, 3: 326-333)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
3
27
0
1
Order By: Relevance
“…Our data clearly show the need for closer attention to anatomical parcellation of the insular cortex–claustrum–lateral striatum region, both in animal studies and in examinations of human functional imaging and clinical pathology. The close apposition of the claustrum with insular cortex and the putamen in primates has been well described (Kapakin, ), but it bears repeating that it is possible to traverse the insular cortex, extreme capsule, dorsal claustrum, and lateral putamen along a linear path of only a few millimeters from the bank of the lateral sulcus, even in the human brain. Furthermore, and potentially even more problematic from the point of view of functional studies, is the commonality of blood supply and venous return among these structures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our data clearly show the need for closer attention to anatomical parcellation of the insular cortex–claustrum–lateral striatum region, both in animal studies and in examinations of human functional imaging and clinical pathology. The close apposition of the claustrum with insular cortex and the putamen in primates has been well described (Kapakin, ), but it bears repeating that it is possible to traverse the insular cortex, extreme capsule, dorsal claustrum, and lateral putamen along a linear path of only a few millimeters from the bank of the lateral sulcus, even in the human brain. Furthermore, and potentially even more problematic from the point of view of functional studies, is the commonality of blood supply and venous return among these structures.…”
Section: Discussionmentioning
confidence: 98%
“…Given the proximity between claustrum and insular cortex and the relatively low resolution of the noninvasive imaging methods that are directly applicable to the human brain, it is uncertain whether the claustrum, anterior insular cortex, or both of these structures originate inputs to salience network areas. The claustrum and insular cortex are not only closely apposed (Kapakin, ) but also share a common arterial blood supply (Marinkovic and Markovic, ; Ture et al, ; Delion and Mercier, ). The venous drainage of the claustrum is also shared with surrounding structures, including the internal, external, and extreme capsules; frontoparietal white matter; and striatum (Zhang et al, ), potentially confounding assignment of functional activity as measured by the BOLD signal (Boubela et al, ).…”
mentioning
confidence: 99%
“…The claustrum is an irregular and fine sheet of grey matter in the basolateral telencephalon present in almost all mammals. The claustrum is separated from the insular cortex by the extreme capsule and medially from the lentiform nucleus by the external capsule (Edelstein and Denaro, 2004;Crick and Koch, 2005;Fernández-Miranda et al, 2008;Kapakin, 2011;Goll et al, 2015;Milardi et al, 2015). Figure 1 shows in an axial view the anatomical location of the human claustrum.…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in the Talairach and Tournoux [] human brain atlas, the claustrum extends 22 mm inferior‐to‐superior and 38 mm anterior‐to‐posterior. The right claustrum has an average volume of 828.83 mm 3 , while the left has a volume of 705.82 mm 3 and lies approximately 1 mm from the insular cortex and about 1 mm from the putamen [Kapakin, ]. Bilaterally, it displays asymmetry in shape and anisotropy between the hemispheres [Cao et al, ] (as shown schematically in Fig.…”
Section: Introductionmentioning
confidence: 99%